Home advantage in soccer: being invincible during home matches may be the reason - Silva, H.; Oliveira, A.; Marcelino, R. (Trends in Sport Sciences, 2025)
Introduction: Previous research has primarily focused on the concept of home advantage, examining the points or wins obtained during home matches.